Normal Knee Joint Spaces in Healthy Young Adults; Radiographic Measurement - Yad Zamin, Motasim Billah, Tariq Ahmad, Nadia Haider, Ayesha Kamran, Sabika Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The weight bearing hinge joint which comprises of two condylar joint is named as knee joint. Objective: The study was carried out to find the radiographic measurements in case of normal knee joints of adults. Study design: It is a prospective study conducted at Orthopedic Department, Mardan Medical Complex and Radiology Department, Institute of Kidney Disease (IKD) Peshawar for the duration of six months from October 2021 to March 2022. Material and Methods: The study was conducted on 170 patients (patients/subjects) who visited the radiology (radiology and orthopedic) department of the hospital. The computerized data was plotted from standard radiographs and the monitoring was carried out to see the progression of degenerative conditions of knee. Statistical analysis was done by using SPSS tool and other software like Microsoft excel were also used for this purpose. The data was shown as mean and standard deviations in case of all variables. The ethical and review board committee of the hospital approved the study. Results: The data was taken from 170 patients. Patients were aware of the study and signed the consent willingly. Among these 170 patients, there were 94 females and 76 males. The average age of the patients participating in this study was 48 ± 13 (38± 13) years. In case of women the average right medial space was 0.25±0.07 (it is mm or cm??) right lateral space was 0.45±0.06, left medial was 0.19±0.08 and left lateral space was 0.44±0.0. In case of male patients, the values of right lateral space, right medial space, left lateral space and left medial space were 0.47±0.07, 0.26±0.05, and 0.47±0.06, 0.23±0.01 respectively. (in other studies normal space is 4.44 medial and 5.62 mm lateral and it is 0.45 and 0.25 mm in our study, I think it shoud be comparable) Conclusion: The study was carried out to find the radiographic measurements of normal spaces of normal knee joint in adults. The AP view was used to observe the bilateral knee joints both medial and lateral sides. The knee joint space width was variable. However, width of left and right side joint space compartments have no difference. There was no statistical variation found between both genders as well. Keywords: Bilateral knee joints, radiographic measurements, joint space compartments, condyles and articular surfaces.